PENGARUH SOCIAL MEDIA MARKETING DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN J.CO DONUTS AND COFFEE KOTA SAMARINDA - Annisa Rinda Rahmawati (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
This study aims: (i) to find out social media marketing variables partially have a significant effect on purchase decisions (ii) to find out word of mouth variables partially have a significant effect on purchase decisions (iii) to find out social media marketing and word of mouth variables simultaneously have a significant effect on consumer purchase decisions at J.CO Donuts and Coffee in Samarinda. This study uses three variables namely social media marketing, word of mouth and purchase decisions. This type of research is a correlation method with a quantitative approach. The population in this research were all consumers of the J.CO Donuts and Coffee in Samarinda whose exact number was unknown and the sampling technique used non-probability sampling with purposive sampling method, the number of samples was 100 respondents. Data collection techniques: field research (observation, online and offline questionnaires) and library research. Then the analysis technique used is multiple linear regression using the test: validity test, reliability test, classic assumption test (normality test, multicollinearity, heteroscedasticity), hypothesis test (partial and simultaneous), multiple linear regression analysis. The result obtained in this study are (i) Social Media Marketing partially had a significant effect on Purchase Decisions (ii) Word Of Mouth partially had a significant effect on Purchase Decisions (iii) Social Media Marketing and Word Of Mouth simultaneously had a significant effect on consumer Purchase Decisions at J.CO Donuts and Coffee in Samarinda.